2020
DOI: 10.1080/00223980.2020.1781033
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Person-Centered Perspective on Positive and Negative Affect at Work

Abstract: This research examines how the direction and intensity of employee's positive and negative affect at work combine within different profiles, and the relations between these profiles and theoreticallyrelevant predictors (psychological need satisfaction and supervisor autonomy support) and outcomes (work-family conflict, absenteeism, and turnover intentions). A total sample of 491 firefighters completed our measures initially, and 139 of those completed the same measures again four months later, allowing us to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 109 publications
(120 reference statements)
11
49
3
Order By: Relevance
“…The present research extends this line of inquiry. It thus complements previous work that applied a person-centered perspective on emotions in various contexts such as work (Sandrin et al, 2020), high school courses (Ganotice et al, 2016;K. A. Robinson et al, 2020), university courses (K. A.…”
Section: Discussion O F T He Fi N DI N G Ssupporting
confidence: 65%
See 3 more Smart Citations
“…The present research extends this line of inquiry. It thus complements previous work that applied a person-centered perspective on emotions in various contexts such as work (Sandrin et al, 2020), high school courses (Ganotice et al, 2016;K. A. Robinson et al, 2020), university courses (K. A.…”
Section: Discussion O F T He Fi N DI N G Ssupporting
confidence: 65%
“…In a laboratory experiment, Siemer et al (2007) showed that participants' emotion profiles in reaction to an ambiguous negative experience were concurrent and naturally aligned with specific sets of cognitive appraisals of the situation. In the work context, Sandrin et al (2020) recently showed the emergence of five distinct profiles of positive and negative affect along with self-perceptions of their impact on job performance. Profiles were relatively stable over time and were meaningfully associated with work-family conflict, absenteeism, and turnover intentions.…”
Section: % 3 0 4 !mentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the five profiles they found in their study, three were found highly stable over time, and two were subjected to very high levels of transitions over time. Not only were our findings related to the anticipation of a future event, but Sandrin et al (2020) used a traitbased view of affect, which makes the comparisons between the two studies extremely difficult. However, it echoes our findings and shows that the replication and similarity of profiles across time points do not preclude individuals from making transitions between some profiles over time.…”
Section: Pr Of I L Es Of Em Ot Io N a L A Nt I Ci P At I On A C Ro S S T Im Ementioning
confidence: 99%